Addressing the psycho-spiritual bereavement needs of HIV and AIDS orphans and other vulnerable adolescents : a narrative pastoral care approach - Muller, Julian C. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.